Understanding discrepancies in perceived importance of patient safety measures between patients and healthcare professionals in perioperative care: An exploratory study - Maria de Lacerda Machado; Ana Beatriz Nunes; Dimey Carvalho; Ana Gama; Carola Orrego; Paulo Sousa (PLoS ONE, 2026)
Background Patient safety is a critical concern in perioperative care. This study explores the discrepancies in how patients and healthcare professionals perceive the importance of perioperative patient safety outcome measures, aiming to improve the development of future Core Outcome Sets (COS). Methods Qualitative exploratory study using focus groups with healthcare professionals and patients involved in the Core Outcome Set for Patient Safety in Perioperative Care. Data were collected through online mini-focus groups and analysed using thematic qualitative text analysis. Results Communication failure emerged as the predominant cross-cutting issue across discussions, particularly in relation to discrepancies in expectations, information exchange, and understanding between healthcare professionals and patients. Three primary reasons for discrepancies in attributed importance of indicators were identified: different targets/focus; knowledge gaps; and varying importance placed on the sense of safety. Patients often emphasized subjective experiences, fears, and emotional impacts, leading them to prioritize quality of life indicators and long-term effects. In contrast, healthcare professionals focused on system-level factors and resource limitations, giving greater weight to technical and physiological outcomes. Discussion/conclusion The study findings underscore the need for a more holistic approach in developing COS, balancing technical medical outcomes with patient-centered quality of life measures.